The Fragility Index of Randomized Controlled Trials for Preterm Neonates - Li, Huiyi; Liang, Zhenyu; Meng, Qiong; Huang, Xin (Frontiers in Pediatrics, 2022)
Background: As a metric to determine the robustness of trial results, the fragility index (FI) is the number indicating how many patients would be required to reverse the significant results. This study aimed to calculate the FI in randomized controlled trials (RCTs) involving preterm neonates. Methods: Trials were included if they had a 1:1 prospective study design, reported statistically significant dichotomous outcomes, and had an explicitly stated sample size or power calculation. The FI was calculated for each trial. The Mann–Whitney U test and Kruskal–Wallis test were used to compare the FIs of groups, and Spearman’s correlation was applied to determine correlations between the FI and study characteristics. Results: Finally, 66 RCTs were included in the analyses. The median FI for these trials was 3.00 (interquartile range [IQR]: 1.00–5.00), with a median fragility quotient of 0.014 (IQR: 0.008–0.028). Forty-two of the RCTs (63.6%) had a FI of less than or equal to 3. In 42.4% (28/66) of the studies, the number of patients lost to follow-up was greater than that of the FI. Significant differences were found in the FI among journals (p = 0.011). We observed that FI was correlated with the sample size, total number of events, and reported p-values (rs = 0.437, 0.495, and −0.857, respectively; all p < 0.001), but not the year of publication (p = 0.442). Conclusions: For premature RCTs, a median of only three events was needed to change from “nonevent” to “event” to render a significant result nonsignificant, indicating that the significance may hinge on a small number of events.